National brand's promotional pricing and advertising policies: spillover effect and quality difference. Issue 12 (2nd December 2022) - Zhu, Guiyang; Chou, Mabel C.; Jia, Tao
Abstract : Considering a channel comprising a national brand (NB) manufacturer and a retailer who sells both the NB and its own store brand (SB) products, this article aims to study the promotional pricing and advertising strategies under an exogenous pricing approach when the two members jointly use consumer promotion and co-operative advertising. Specifically, this article explores how both the spillover effect of advertising and the quality difference between the brands affect the equilibrium outcomes and the NB manufacturer's profits. Several results are obtained: (1) as long as the spillover effect is lower than a threshold, both channel members will participate in the promotion campaign; (2) a higher spillover effect improves the NB manufacturer's profit by not only enhancing her revenue but also reducing her advertising cost; and (3) a larger quality difference also increases the NB manufacturer's profit, by growing her revenue more quickly than her advertising cost.